Eco-spiritual Well-Being: Exploring Flora’s Psychological Impact through the Lens of the Qurʾan and Contemporary Research - Munirah Abd Razzak (Al-Bayān, 2025)
The rising prevalence of mental health challenges among Generation Z calls for a more holistic and faith-integrated approach to well-being. While modern research increasingly recognizes the psychological and physiological benefits of nature, a significant gap remains in connecting these findings with Quranic insights. This study seeks to bridge that gap by exploring the role of flora in promoting mental and emotional health through an integrative lens that combines Quranic wisdom and contemporary scientific literature. Specifically, the study aims to explore Quranic references that highlight the role of plants in promoting human well-being, examine contemporary scientific research on the psychological and physiological benefits of flora, and synthesize these spiritual and empirical insights to develop a comprehensive understanding of how nature can support the mental well-being of Generation Z. The expected outcome is a faith-based yet evidence-informed model for mental well-being that is culturally and religiously sensitive. This interdisciplinary approach aims to inform practical strategies for educators, policymakers, and mental health practitioners, especially in designing interventions tailored to the needs of Generation Z. By integrating spiritual and scientific insights, the study contributes to the broader discourse on faith, psychology, and environmental well-being, with potential applications in faith-based counselling, environmental psychology, and sustainable urban planning. This integrated model is designed to contribute meaningfully to the discourse on faith and psychology, while also offering practical insights for policymakers, educators, and mental health practitioners in crafting interventions tailored to the unique needs of Generation Z. The broader significance of this research lies in its interdisciplinary approach, which not only advances current knowledge of flora’s role in supporting mental health but also promotes culturally and religiously sensitive perspectives on well-being. Ultimately, the study aspires to inform innovative practices in faith-based counselling, environmental psychology, and sustainable urban planning, with the overarching goal of enhancing quality of life for future generations.